Reading Pattern (Superficial - Deep) and its Relationship to Reading Comprehension Among Students of Arabic Language Departments in Colleges of Education for the Humanities - ALWAISAWI, SHAHAD FADHIL KHUDAIR; Al_ASADI, BASSAM ABDULKHALEQ ABBAS (Journal of Ecohumanism, 2025)
The researcher complied a descriptive, correlational approach to carry out the research objectives. This approach is centered on providing a precise and comprehensive description of phenomena and analyzing, interpreting, and balancing the data. The research population for this study involves fourth-stage students in the colleges of education for the humanities at the universities of Babylon, Kufa, Al-Qadisiyah, Karbala, Wasit, Baghdad, and Al-Mustansiriya for the academic year 2023-2024. The total number of students in this population is 697, including 189 male students and 508 female students. The researcher utilized the Stephen Thompson equation to select a sample from the total research population. Therefore, 346 students have been selected, including 127 males and 219 females. To fulfill the research objectives, the researcher selected Geraldine equation 2007 to measure reading pattern which includes (12) items. It was viewed by (21) experts to verify the validity of its items. Then the psychometric properties of the scale and the statistical indexes were extracted to be ready for application. The second tool is the reading comprehension test. The researcher selected a number of texts and presented them to (21) experts and arbitrators. The researcher applied the Chi-square for good matching to confirm the validity of the text for the research sample. Then the researcher applied the test to an exploratory sample of (46) male and female students.